Antioxidant Activity Test on Ethanol Extract Of Soursop Leaves (Annona muricata L.) Using DPPH Method (1,1-diphenyl-2-picrylhidrazyl) - Abdul Gani; Ratih Delviyanti; Rusman Rusman (Department of Chemical Education Faculty of Teacher Training and Education Universitas Su, 2021)
Soursop plant parts that are often used by the community, namely the fruit and leaves. Ripe soursop fruit is usually developed to produce juice and lunkhead products. Ripe soursop fruit contains vitamin C which is known to have a wrong function, namely to increase immunity, so that it can protect the body from pathogens. Soursop leaves are often used by the community in the form of a decoction of the leaves for traditional medicine. The research about antioxidant test on ethanol extract of soursop leaves (Annona muricata Linn) had been conducted using DPPH method (1,1-diphenyl-2-picrylhdirazyl). This research aims to indicate the antioxidant activity of soursop leaves. Samples were collected from Lambaro Skep, a region of Banda Aceh. Then, the sample was dried by air before macerated using ethanol 96%. After that, the filtrate is evaporated using rotary evaporator and concentrated again using a hairdryer. The concentrated extract is then tested for antioxidant activity using DPPH method at maximum wavelength of 517 nm. The result shows young soursop leaves extract has 14.462 ppm of IC50 value, while old soursop leaves extract has IC50 value of 9.626 ppm.